Turkey and Britain: from enemies to allies, 1914–1939. Issue 5 (3rd September 2018) - MacArthur-Seal, Daniel-Joseph
ABSTRACT: The relationship between Turkey and Britain shifted dramatically in the first three decades of the twentieth century, with the one-time diplomatic defender of Ottoman integrity emerging as its most formidable foe during the First World War and War of Independence. Despite this history of enmity, Turco–British relations entered a period of remarkable recovery in the years after 1923 as potential areas of conflict, such as the status of Mosul province and militarisation and access to the Dardanelles and Bosphorus, were resolved. Nevertheless, recriminations with their origins in this crucial period of the collapse of the Ottoman Empire and foundation of the Turkish Republic lingered, sustaining suspicions over British intentions towards Turkey and its neighbours up until the present. Perhaps surprisingly, the UK–Turkey relationship has remained notably cordial in the midst of growing diplomatic hostility between Turkey and its Nato partners over the past two years. In a special issue of Middle Eastern Studies, historians re-examine diplomatic, economic, cultural, and intellectual connections between the two countries during the period 1914–1939, advancing historical scholarship on this crucial relationship through the use of sources from Turkey, Britain, and further afield.